2002
DOI: 10.1080/00288233.2002.9513508
|View full text |Cite
|
Sign up to set email alerts
|

Sire effects on antibodies to nematode parasites in grazing dairy cows

Abstract: A study was carried out on New Zealand dairy cows at pasture, to test for evidence of genetic differences in immunological response to nematode parasites. Nine widely used HolsteinFriesian artificial insemination bulls, with daughters in many herds, were evaluated for nematode antibodies by sampling milk of their daughters in mid lactation in each of 20 North Island herds. One milk sample was taken from each cow (ranging from 4 to 11 years of age), during a routine herd test in the period from mid November 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…The Abs were also highly correlated amongst themselves, as also reported by Agneessens et al (2000) in a Belgian study, with a high correlation (R = 0.72) between Abs to adult Cooperia and Ostertagia species, and by Morris et al (2002) in a New Zealand study with grazing dairy cows, where four of the same six Abs as in the present study had a similar high correlation (averageR = 0.81). Bissetetal.…”
Section: Studysupporting
confidence: 80%
See 2 more Smart Citations
“…The Abs were also highly correlated amongst themselves, as also reported by Agneessens et al (2000) in a Belgian study, with a high correlation (R = 0.72) between Abs to adult Cooperia and Ostertagia species, and by Morris et al (2002) in a New Zealand study with grazing dairy cows, where four of the same six Abs as in the present study had a similar high correlation (averageR = 0.81). Bissetetal.…”
Section: Studysupporting
confidence: 80%
“…One method may be the genetic approach, utilising the natural ability of some animals to resist high levels of parasitic infection or their effects. Heritable differences in parasite-related traits have been reported in New Zealand, both in dairy cattle (Morris et al 2002) and in beef cattle (Morris et al 2003), in all stock classes studied so far. These include: faecal egg count (FEC) in beef calves at 7-10 months of age, and anti-nematode antibody (Ab) concentrations in four stock classes, beef calves, yearling beef heifers, peri-parturient beef cows, and mid-lactation mixed-age dairy cows.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Vanimisetti et al (2004) reported 0.10 and 0.19 h 2 in lambs of 50% Dorset, 25% Rambouillet and 25% Finnsheep ancestry and 0.31 h 2 in ewes of same sheep. Higher estimates were reported by Morris et al (2000) in Romney sheep (0.29±0.02 to 0.36±0.02), Bishop and Stear (2001) in Scottish Blackface sheep (0.23±0.05), Woolaston and Windon (2001) in Merino sheep (0.21±0.06 to 0.38±0.04) and McEwan et al (1995), Douch et al (1995), Morris et al (2002) in New Zealand sheep breeds (0.20± 0.07 to 0.42±0.10). Addition of maternal genetic effect reduced the h 2 estimates by 24.8% in model 2.…”
Section: Genetic Studiesmentioning
confidence: 59%
“…This β-casein study was part of a larger project carried out with milk from 21 large dairy herds in the upper North Island of New Zealand, described earlier by Morris et al (2002). The average herd size in the main project was about 750 cows, over three times the national average at the time.…”
Section: Trial Designmentioning
confidence: 99%